Magnitude of sympathovagal imbalance and its correlation with inflammatory response and oxidative stress in pregnant women at risk of pregnancy induced hypertension: a cross-sectional study - K., Vidya Karpagam; Pal, Gopal Krushna; Habeebullah, Syed; S., Velkumary; R., Soundaravally (International Journal of Research in Medical Sciences, 2024)
Background: Pregnancy-induced hypertension (PIH) is a common complication of pregnancy but it’s genesis isn’t known. It is proposed to be due to an excessive inflammatory response in the mother secondary to placental or maternal factors. The study aimed to measure the magnitude of sympathovagal imbalance (SVI) and to evaluate the role that oxidative stress and the inflammatory response play in the development of sympathovagal imbalance in pregnant mothers with risk factors of pregnancy-induced hypertension. Methods: A cross-sectional study was carried out among pregnant women with at least one risk factor for PIH and age-matched pregnant women without risk factors for PIH as controls from March 2023 to February 2024 in a tertiary care hospital in Pondicherry. The intergroup differences in the mean between the two groups were compared using the Mann Whitney test and the Student’s T-test. Results: Short-term heart rate variability was significantly higher among cases while time domain analysis didn’t show significance. Total Cholesterol (TC), Triglycerides (TG), Very Low-Density Lipoprotein (VLDL) and Low-Density Lipoprotein (LDL) were significantly higher among the cases and High-Density Lipoprotein (HDL) was low in cases compared to controls. There is a strong correlation of Low Frequency to High Frequency (LF-HF) ratio with Tumor Necrosis Factor-alpha (TNF-α) and high sensitivity (hs-CRP) in patients with risk factors of PIH. Conclusions: Pregnant women at risk of pregnancy-induced hypertension showed increased inflammatory response, oxidative stress and dyslipidaemia. Hence, conducting sessions for stress management not only during pregnancy but also in the pre-pregnancy period can alleviate sympathetic dysfunction.